Pemberdayaan Masyarakat Melalui Pelatihan Handycraft Kulit Kerang Untuk Meningkatkan Perekonomian Rumah Tangga di Banjar Kemuning Sedati Sidoarjo - Yayu Sriwahyuni Hamzah; Budi Purwantiningsih; Mukhlis Irfan Ariadi (LPPM Universitas Yudharta Pasuruan, 2019)
Banjar Kemuning Village, most of which are located on the coast, should use a lot of this potential to develop MSMEs. One of the potentials that can be found in coastal areas is seashells. Although the potential for shells is found in Banjar Kemuning Village, shellfish crafts have not been touched to develop at all. To realize the expected conditions of the assisted subjects, the method in this empowerment program uses Asset-Based Community Development (ABCD). The implementation of devotion for coastal communities can be concluded successfully until the training stage of making nine forms of shell shell crafts. 80% of participants have understood the process of processing shells into high-value craft, so that the use of natural resources to improve the family economy at times especially low season can be achieved.